The Value of Struggle to Reach Goals in Buku Besar Peminum Kopi by Andrea Hirata Novel and Its Relevance to Indonesian Language Learning in Senior High Schools - Arumda, Larasaji Narindri; Nuryatin, Agus; Nugroho, Yusro Edy (Universitas Negeri Semarang, 2023)
The Novel Buku Besar Peminum Kopi by Andrea Hirata presents an interesting story about the process of achieving the goal of becoming a chess champion and wanting to beat the defending champion. The purpose of this study is to describe the value of the struggle for the ideals contained in the novel and its relevance to learning Indonesian in senior high school. This study used qualitative descriptive method with data collection techniques using heuristic and data analysis techniques using hermeneutic. The data in thing research is in the form of discourse which shows the value of struggle to reach the ideals contained in the novel, the value of self-sacrifice, the value of unity, the value of respect, the value of cooperation. Which can be relevant to learning Indonesian in senior high school with KD 3.9 analyzing the content and language of the novel.